Interactions entre pairs dans des échanges ordinaires: pratiques conversationnelles de jeunes enfants entre eux - Delamotte-Legrand, Régine (Travaux neuchâtelois de linguistique, 2008)
As far as children's interactions are concerned, research have more often focused on exchanges between adults and children than between children. However, researchers on language acquisition all agree on the irreplaceable and original role of these exchanges for the children language development. The purpose of my contribution is to analyze how those exchanges work. My specific interest is the discursive competences of young children in conversations. The following examples are extract from verbal interactions between children, recorded without any adult intervention, under ordinary conditions of language use.